2017
DOI: 10.1007/s11010-017-3012-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of AP-1 transcription factors in human prostate LNCaP and PC-3 cells: role of Fra-1 in transition to CRPC status

Abstract: Androgen receptor (AR) signaling axis plays a vital role in the development of prostate and critical in the progression of prostate cancer. Androgen withdrawal initially regresses tumors but eventually develops into aggressive castration-resistant prostate cancer (CRPC). Activator Protein-1 (AP-1) transcription factors are most likely to be associated with malignant transformation in prostate cancer. Hence, to determine the implication of AR and AP-1 in promoting the transition of prostate cancer to the androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…These ndings agree with earlier studies reported. 6,25 One of studies reveals that the mechanisms of BCT-induced apoptosis in androgen-independent prostate cancer cells is partially reliant on calpain activity and pan-caspase inhibition. 31 However, the detailed molecular mechanisms of how bicalutamide inhibits the growth of androgen-independent prostate cancer cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings agree with earlier studies reported. 6,25 One of studies reveals that the mechanisms of BCT-induced apoptosis in androgen-independent prostate cancer cells is partially reliant on calpain activity and pan-caspase inhibition. 31 However, the detailed molecular mechanisms of how bicalutamide inhibits the growth of androgen-independent prostate cancer cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with previous studies. 6,24,25 NBT or BCT at 20-50 mM concentrations had small to moderate effects on prostate cancer cells, which allow us to determine the potential synergistic effect of combinations of the two compounds. Therefore we chose 20-50 mM for combination studies.…”
Section: Treatment With Nbt or Bct Reduces The Viability Of Both Pc-3mentioning
confidence: 99%
“…Constitutive AP-1 activity in PCa disease is associated with poor clinical outcomes through modulating cancer-related genes expression involved in inflammation, cell proliferation, neoplastic transformation and metastasis [181][182][183]. Studies have reported that the correlation between Fos (Fra-1) and Jun family (c-Jun) proteins has been associated with tumour growth in multiple types of cancer.…”
Section: Activating Protein-1 (Ap-1)mentioning
confidence: 99%
“…Other studies reported that the increased cytoplasmic phosphorylated ATF proteins family (ATF2) in PCa compared to normal prostate cells suggest that altered localisation of ATF2 may contribute to clinical progression of PCa [187]. Meanwhile, the activation of the member of Fos family (Fra-1) and Jun family (c-Jun) proteins have associated with the progression to AIPC state [182,188]. Elevated levels of Jun and Fos proteins in mouse models of PCa was also correlated with prostate tumorigenesis, whereas the levels of Jun proteins alone is correlated with disease recurrence [189].…”
Section: Activating Protein-1 (Ap-1)mentioning
confidence: 99%
“…The activation of AP-1 is regulated by MAPK. The activation of each member of the MAPK subfamily has a specific phosphorylation cascade (Kavya et al, 2017). ERK pathway regulates cell growth and differentiation.…”
Section: Activation Of Mapk and Cyclin D1/cdk4 In Malignant Transformmentioning
confidence: 99%